Monetary policy and its impact on stock market liquidity: Evidence from the euro zone - Octavio Fernández-Amador; Martin Gächter; Martin Larch; Georg Peter (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2011)
The recent financial crisis has been characterized by unprecedented monetary policy interventions of central banks with the intention to stabilize financial markets and the real economy. This paper sheds light on the actual impact of monetary policy on stock liquidity and thereby addresses its role as a determinant of commonality in liquidity. To capture effects both at the micro and macro level of stock markets, we apply panel estimations and vector autoregressive models. Our results suggest that an expansionary monetary policy of the European Central Bank leads to an increase of stock market liquidity in the German, French and Italian markets. These findings are robust for seven proxies of liquidity and two measures of monetary policy.
Keywords: E44; E51; E52; G12; 330; Stock liquidity; monetary policy; euro zone; Geldpolitik; Marktliquidität; Europäische Wirtschafts- und Währungsunion; EU-Staaten